Justification of the Reduction Possibility of Sulfur Oxides and Fly Ash Emissions during Co-Combustion of Coal and Waste from Woodworking Enterprises - Stanislav Yankovsky; Anton Tolokol’nikov; Alexander Gorshkov; Albina Misyukova; Geniy Kuznetsov (Applied Sciences, 2021)
In this work, we experimentally investigated the effect of widespread biomass (woodworking waste—pine sawdust) in the composition of mixed fuel, formed also using the widespread steam coals metalignitous (D) and lean (T), on the concentration of sulfur, nitrogen and carbon oxides in flue gases. Investigations of composite fuels with a mass of at least 5 g were carried out in a reactor with continuous recording of the composition of the flue gases formed during the thermal decomposition of the investigated fuels. Thermal decomposition of fuels was carried out in the temperature range from 293 K to 873 K. It was found that an increase in the proportion of wood components in mixed fuels based on two different coals from 10% to 50% leads to a significant decrease in the concentration of sulfur oxides from 11% to 95.8% relative to the concentration of the formation of sulfur oxides in a homogeneous coal, respectively. It was found that an increase in the proportion of the wood component in the mixture with grade D coal up to 50% leads to a significant increase in the content of calcium sulfates (45.1%) and aluminum (43.2%) in the blended fuel. The increase in the content of these salts in the ash of mixed fuels based on T coal and wood is 35.1% and 38.6%, respectively. The obtained research results allowed us to conclude that woodworking wastes are an effective addition to the coals of various deposits, which would help to reduce anthropogenic-induced gas emissions when they are co-combusting in the furnaces of power boilers.